The Significance of Pragmatism in Educational Research: A Current Perspective - King , Rosalyn (Research Highlights in Language, Literature and Education Vol. 3, 2023)
The purpose of this chapter is to explain why the pragmatic approach is useful to educational researchers. The articles objectives will address the major contributory thinkers of Peirce, James, and Dewey; detailing the philosophy of pragmatism, the pragmatic maxim, and its philosophical assumptions, albeit theoretical position – at odds with the ontologies and epistemiologies of positivism and constructivism. A summary will then explore how pragmatism shows ontological and epistemological awareness although is best considered a methodology. The article addresses through example of an educational research inquiry how pragmatic methodology does not reduce all social scientific knowledge to mere binary assumption, and how epistemologically and ontologically it differs from its competitors, in fulfilling its research inquiry. The article concludes with a distinction between the Peircean pragmatism theorists and that of contemporary pragmatism, whilst challenging the ulitity of such approaches, for the benefit of the researcher and practitioner alike.